Identification of suitable WA-CMS lines using morphological and molecular marker analysis in rice (Oryza sativa L.) - Roy, Chandan; Deo, Indra (ORYZA-An International Journal of Rice, 2018)
Hybrid rice has tremendous potentiality to increase the on farm produce by maximizing the per-capita production. In India, yield potentiality of hybrid rice has not been achieved like China, suggesting the development of moreheterotic hybrids adaptable for different agro-climatic region. Development of ideal parental lines is crucial to derive highly heterotic hybrids. Ten cytoplasmic male sterile (CMS) lines were developed into different genetic background of rice and evaluated after five back cross in randomized complete block design with three replications in the year 2010-11 and 2011-12 to identify suitable parental lines for hybrid development. All the lines except IR62871-325-3A showed complete pollen sterility (>85%), among them IR 62871-325-3-1A, UPRM 78-4-1A and UPRM 271-8-5EUI 3-3A were 100% pollen sterile. UPRM 78-4-1A showed 92.1% stigma exertion and early maturity. UPGMA (Unweighted Pair Group Method with Arithmetic Mean) cluster analysis based onmolecular marker data grouped UPRM 78-4-1 and IR 62871-325-3-1 into two separate clusters (similarity coefficient 0.54). Considering morphological characteristics and cluster distance UPRM 78-4-1A, UPPRM 271-8-5EUI-3-3A and IR 62871-325-3-1A were identified as most suitable male sterile lines for hybrid rice breeding. Present findings may be useful for the development of new hybrids using these lines as female parent.